Analisis Kebebasan Bermedia Sosial Pada Penyebaran Informasi Publik Bermuatan Penghinaan dan Pencemaran Nama Baik - Amri Teguh Ramadhan; Ashabul Kahfi (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
The crime of insulting and / or defamation is regulated in articles 310-311 of the Criminal Code. Criminal acts of humiliation and / or defamation through social media are regulated in article 27 paragraph 3 of Law Number 19 of 2016 concerning Electronic Information and Transactions which is an extension of articles 310-311 of the Criminal Code in cyberspace. This concerns how the juridical provisions for criminal acts of defamation and / or defamation and how to enforce the law against perpetrators of criminal acts of insult and / or defamation. Article 27 Paragraph 3 of Law Number 19 Year 2016 concerning Electronic Information and Transactions is required for perpetrators of criminal acts of defamation and / or defamation either in cyberspace or cyber. The explanation regarding the provisions of Article 27 Paragraph 3 of Law Number 19 Year 2016 concerning Electronic Information and Transactions refers to the provisions of Articles 310-311 of the Criminal Code. As well as the decision of the Sungguminasa District Court Number: 278 / Pid.Sus / 2019 / PN Sgm Year 2019 that the indictments of the public prosecutor and the judges' decision are correct, and a 2-month imprisonment sanction that does not need to be served with a probationary note of 4 months as well. late right. Because the defendant as a village head has a big responsibility towards his people and the spirit of the village head must also be guarded.